Analysis Of Receiving Service Quality To Improve Employee Per-formance In The Kitchen & Housekeeping Department At Renais-sance Hotel Bali Uluwatu Resort & Spa - Sukma Cahyana, I Kadek; Wendri, I Gusti Made; Sagitarini, Luh Linna (Jurnal Sains Terapan Pariwisata, 2022)
Purpose: Receiving services are the main thing in receiving and distributing materials. Therefore, the production of kitchen and housekeeping departments is very dependent on receiving, which may impact the performance of the employees themselves.Research methods: This research is quantitative, with primary data collected by questionnaires, observations, and document studies. Data was collected by distributing 30 questionnaires to kitchen and housekeeping employees. This study uses a multiple regression method where the dependent variable is employee performance, and the independent variable is service quality, which consists of 5 dimensions, namely tangible, reliability, responsiveness, assurance, and empathy.Results and discussion: Based on the results of the questionnaire using the t-test (partial test), the service quality variables that have a significant influence on the performance of kitchen and housekeeping employees are tangible, reliable, and assurance. At the same time, the variables of responsiveness and empathy do not have a significant effect on the performance of kitchen and housekeeping employees.Implication: Based on the f-test in examining the effect simultaneously, it shows that all variables of reliability, responsiveness, assurance, and empathy jointly affect the performance of kitchen and housekeeping employees.